SISTEM INFORMASI LAPORAN DATA PERTAMBANGAN PADA DINAS PERTAMBANGAN DAN ENERGI TEMBILAHAN BERBASIS WEB - Budi Aprianto (Sistemasi: Jurnal Sistem Informasi, 2013)
The need for an information system today includes almost in every scope of life . Every organization is in need of accurate, fast and relevant . But in reality it is sometimes not in accordance with the wishes and expectations will be achieved , due to the lack of or limited use of information systems . So it is with the need for a system processing and delivery of good data can no longer be postponed , given the things that have been described previously . But in reality all activities related to data collection information on the Mining and Energy offices are still using Microsoft Office Excel, where the system pendataannya less efficient due to numerous data collection that relate to mining activities . The author in this case choosing the Mining and Energy offices in conducting his research, to reveal a better development in various fields who lived , especially in information and communication technology . Keywords : data, reports and mining